2005
DOI: 10.1158/1055-9965.epi-04-0197
|View full text |Cite
|
Sign up to set email alerts
|

Cyp17, Urinary Sex Steroid Levels and Breast Cancer Risk in Postmenopausal Women

Abstract: Endogenous sex hormones play an important role in the etiology of breast cancer. Polymorphisms in genes encoding for enzymes involved in steroidogenesis may therefore play a role in breast cancer risk. Cytochrome P450c17a (Cyp17) functions at key branch points in human steroidogenesis. A T! !C transition (A1 and A2 allele) in the 5V untranslated region may be associated with increased expression of Cyp17. Using a case-cohort design, we studied the effects of the A2 allele on endogenous sex hormone levels and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
5
0
4
Order By: Relevance
“…We thus examined associations between CYP17 genotypes and hormone-related risk factors, and we found that the CYP17 C variant genotypes were associated with breast cancer among women with pregnancy times [2, or with high BMI (C23 kg/m 2 ), or with breastfeeding \12 months. Interestingly, a report from a similar size of study showed that women with low BMI and the A2A2 (CC) genotype had higher endogenous sex steroid levels, but this did not translate into an increased breast cancer risk [23], further underscoring the multi-factorial effect in determination of breast cancer risk. Aromatase is the enzyme responsible for catalyzing the final step of conversion of androgens into estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…We thus examined associations between CYP17 genotypes and hormone-related risk factors, and we found that the CYP17 C variant genotypes were associated with breast cancer among women with pregnancy times [2, or with high BMI (C23 kg/m 2 ), or with breastfeeding \12 months. Interestingly, a report from a similar size of study showed that women with low BMI and the A2A2 (CC) genotype had higher endogenous sex steroid levels, but this did not translate into an increased breast cancer risk [23], further underscoring the multi-factorial effect in determination of breast cancer risk. Aromatase is the enzyme responsible for catalyzing the final step of conversion of androgens into estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings may contribute to the increased risk in women with C allele and early age at menarche. Finally, CYP17 C carriers in post-menopausal women were thought to be positively related to high BMI [30], thereby having high hormone levels [63]. Under this premise, they may be more susceptible to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no evidence of association of genotype with serum levels of androgens, the precursors of estrogens (Figure 1). Higher levels of estrogens in women with the C allele have been reported in saliva [27], urine [28], and follicular fluid [29]. The association of the variant with higher levels of estrogen found in some studies would lead to the hypothesis that it would increase risk of endometrial cancer, in contrast to the reductions in risk noted in this and some other studies.…”
Section: Discussionmentioning
confidence: 55%